PENGARUH MOTIVASI TERHADAP PENINGKATAN KINERJA PEGAWAI DINAS PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN NIAS - SUDARMAN ZEBUA; EMANUEL ZEBUA; NOVELINA ANDRIANI ZEGA (JURNAL ILMIAH SIMANTEK, 2022)
This research was conducted to determine the effect of motivation on improving employee performance at the Department of Tourism, Youth and Sports in Nias Regency. The population and sample in this study were 26 employees within the scope of the Office of Tourism, Youth and Sports of Nias Regency. Data collection was carried out by distributing questionnaires. The type of research used is descriptive quantitative where the data analysis technique used is the classical assumption test with simple linear regression analysis. The research results after verification were used as a questionnaire and processed through IBM statistical for product and service solution (SPSS) version 20 for windows. Based on the results of the validity test where r count > r table with a significant level of 5% r table, namely 0.404, it was stated that all items were valid with the results of the Cronbach alpha reliability test variable X = 0.669 and variable Y = 0.686 where the standard error was 0.60 meaning that the test items repeatedly get a consistent value and declared reliable. To see the relationship, a correlation coefficient test was carried out and it was found that R = 0.687, meaning that motivation has a strong relationship with employee performance at the Tourism, Youth and Sports Office of Nias Regency. The results of simple linear regression analysis obtained Y = 8.266 + 0.714 X, meaning that every time there is an increase of one unit in the motivational variable (X) it will be followed by an increase in employee performance (Y) of 0.714. The determinant coefficient is r² = 0.471, which means that 47.1% of the Motivation Variable (X) affects the Employee Performance variable (Y) at the Office of Tourism, Youth and Sports of Nias Regency. Hypothesis testing was carried out by a t test of t count 4.627 > t table 1.710 with a significant level of 0.000 <0.05 (5%). This means that the hypothesis is proven where Ha is accepted and Hᴼ is rejected